Effect of Foliar Application with Nano-Organic Fertilizer and Proline Acid and their Interaction in Leaf Content of Antioxidants and Vitamin D3 for Moringa oleifera - Faten Khalifa Kareem1 , Mahmood A. Al Shaheen2 (Indian Journal of Forensic Medicine & Toxicology, 2020)
A potted pot capacity 15 kg experiment was carried out during the agricultural season 2019 in one of theprivate nurseries of Al-Ramadi / Anbar Governorate, to study the effect of foliar application of nano-fertilizerand proline acid on the content of antioxidants and vitamin D3 for Moringa oleifera leaves using sandy mixsoil. The experiment was designed using Completely Randomized Design (CRD) with three replications. Thestudy included three concentrations of nano-organic fertilizer (0, 50, 100) mg-liter-1 and three concentrationsof the amino acid proline (0, 100, 200) mg-1 . after 150 days from the date of seed germination the leafcontent of vitamin C was measured and phenols using the least significant difference LSD at 0.05 probabilitylevel. Qurcetine flavonoids, Rutine flavonoids and vitamin D3 were measured according to the T test totest the differences between the averages of the treatments. The results showed that the nano-fertilizer atconcentration100 mg L1 achieved the highest antioxidant level that included vitamin C, phenol, flavonoidquercetin, flavonoid routine and achieved the highest average vitamin D3 content. And that treatment withproline acid at a concentration of 200 mg / L -1 achieved the highest antioxidant content (vitamin C, phenols,Qurcetine and Rutine flavonoids) in addition to vitamin D3. The interaction between the study two factorshad a positive effect on most of the rates of the studied traits. The plants which treated with (100 mg-liter-1nano organic fertilizer and 200 mg-liter-1-proline acid) gave the highest rate of leaf content of vitamin C,phenols, Qurcetine, and Rutine flavonoids, while treatment with ( 100 mg-liter-1 nano organic fertilizer and100 mg-1-proline acid) has achieved the highest leaf content level of vitamin D3 .